Analysis of International Measures to Reduce the Environmental Pollution caused by Oil Tankers - Alireza Ansari Mahyari; Hadi Mahmoudi (Jurídicas)
Due to the high use of the sea and the diversity and speed of discharge of pollutants into the sea nowadays, the self-purification capacity of marine ecosystems is reduced, and the effects of the entry of these substances can hardly be neutralized. Various human activities through maritime transport have led to the entrance of oil pollutants through current ship operations and maritime accidents. This paved the way for the emergence of a global mindset on the need to protect the marine environment from oil pollution and take actions to prevent, cooperate and deal with pollution, and, ultimately, to compensate the victims of these accidents. The purpose of this study is to research the impact of international actions taken to reduce the environmental pollution from oil tankers. This article has been carried out using a descriptive-analytical method. Based on studies conducted, the authors conclude that international rules and regulations have defined the limits of the rights and obligations of governments and international organizations in reducing environmental pollution from oil tankers. What needs to be done is to find universal support for these rules and regulations and their implementation. The perfect implementation of International Conventions for the proper transportation, collection, recycling, treatment, processing, and disposal of these materials will have a significant effect on the reduction of marine pollution caused by maritime transport.